A type-2 fuzzy rule-based model for diagnosis of COVID-19 - Sahin, Ihsan; Akdogan, Erhan; Aktan, Mehmet Emin (Tubitak Scientific & Technological Research Council Turkey, 2023)
In this study, a type-2 fuzzy logic-based decision support system comprising clinical examination and blood test results that health professionals can use in addition to existing methods in the diagnosis of COVID-19 has been developed. The developed system consists of three fuzzy units. The first fuzzy unit produces COVID-19 positivity as a percentage according to the respiratory rate, loss of smell, and body temperature values, and the second fuzzy unit according to the C-reactive protein, lymphocyte, and D-dimer values obtained as a result of the blood tests. In the third fuzzy unit, the COVID-19 positivity risks according to the clinical examination and blood analysis results, which are the outputs of the first and second fuzzy units, are evaluated together and the result is obtained. As a result of the evaluation of the trials with 60 different scenarios by physicians, it has been revealed that the system can detect COVID-19 risk with 86.6% accuracy.
Keywords: COVID-19; fuzzy logic; decision support system; diagnosis; INTERVAL TYPE-2; FRAMEWORK; SEVERITY; SYSTEMS; DRIVEN; Computer Science; Engineering